Knowledge, Attitude, and Practice of Livestock Owners and Livestock Assistants towards African Trypanosomiasis Control in The Gambia - Alpha Kargbo; Edrisa Jawo; Amien Isaac Amoutchi; Herve Koua; Rex Kuye; Zainabou Dabre; Abdoulie Bojang; Rafael F. C. Vieira (Journal of Parasitology Research)
Background. In Africa, it has been estimated that 50 million cattle and 70 million sheep and goats are at risk of animal African trypanosomiasis, and three million cattle die annually. Methods. This study was conducted in all the regions of The Gambia except Kombo Saint Mary Island (Banjul). Structured questionnaires were administered to 440 randomly selected livestock owners and 23 livestock assistants, and 7 focus group discussions were held for both livestock owners and livestock assistants. The data were analyzed mainly using descriptive statistics and content analysis methods. Results. A total of 94.5% and 75% of livestock owners reported having seen tsetse and horse flies, respectively, while 100% of livestock assistants reported having seen tsetse flies. Forty-seven percent of the livestock owners indicated a positive attitude toward control measures, while 42% of them had no idea how to control tsetse flies. On the other hand, 57% of livestock assistants believe that tsetse and horse flies are the main reasons why AAT is still in their community. There was a statistically significant difference between all the respondents’ characteristics and the practices done by livestock owners to prevent AAT vectors from biting their animals. Conclusion. This study shows that trypanosomiasis is still a major problem for livestock health and production in The Gambia, and it requires disease and vector control.